Identifying Risk Factors for Impaired Pulmonary Function in COVID-19 Patients: Cross-Sectional Study - Bayaraa, Odonchimeg; Myeryemkhaan, Allabyergyen; Jamsran, Gaamaa; Boldbaatar, Norjmaa; Jav , Sarantuya; Sonomjamts, Mukhbayarlakh; Dashtseren, Ichinnorov (Central Asian Journal of Medical Sciences, 2025)
Objective: COVID-19 has an impact on various organs, including heart, kidney, lung, and liver. However, respiratory system has been the primary organ mostly affected, ranging from asymp tomatic to critical stages of the disease. The risk of developing impaired pulmonary function depends on multiple factors, including demographic and clinical manifestations such as severi ty of the disease, comorbidities, and treatment options. As the number of new COVID-19 cases declines, public health experts and medical doctors are increasingly interested in conditions after COVID-19 and are working to improve the quality of life for affected patients. Our study aim was to investigate risk factors associated with impaired pulmonary function in individuals recovered from severe COVID-19. Method: The study was conducted using a hospital-based, cross-sectional study design. A total of 268 participants who visited the Pulmonology and Allergology Center of The First Central Hospital of Mongolia for a follow-up examination one year after contracting COVID-19 between 2022 and 2023. Demographic data, comorbidities, severity of initial infection, hospitalization history, and spirometry were analyzed to determine their association with post-COVID-19 impairment of pulmonary function. Results: This study identified the risk factors significantly associated with altered pulmonary function in post COVID-19. 50.4% of individuals with initial severe infection had altered pulmonary function. Severe group had higher odds of decreasing FVC (predicted %) compared to the asymptomatic group (OR=3.69; 95% CI; P =0.003). For comorbidities, patients with cardiovascular disease were significantly more likely to decrease FVC (predicted %) compared to participants who had no comorbidities (OR=4.22; 95% CI; P =0.040). Moreover, patients with chronic lung diseases had a significantly high of impaired FVC (%), with an adjusted odds ratio of 2.46 (95% CI, P =0.005) Conclusion: Patients with pre-existing cardiovascular and chronic lung diseases, and severe initial infection have a significantly higher likelihood of impaired pulmonary function compared to those with other comorbidities, and non-severe COVID-19.